Integrasi Alquran pada Mata Kuliah Trigonometri - Ahmad, Herlina; Febryanti; Tasni, Nurfaida (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2020)
The ideal values in character education that play the most role are the values of religious teachings, this is the basis of research on the integration of Alquran in trigonometry courses. This research aims to see the influence of the integration of the Qur'an on trigonometric courses on student learning outcomes. The type of this research is mix-method. This research begins by compiling a draft of 4 chapters that are integrated with Alquran, namely surah Al Anbiya ayat 30, Al-Hujurat verse 13, Adz-Dzariat verse 56, Al-Baqarah verse 142-145 and Surah Yunus verse 87 and the success phytagoras approach. Based on qualitative data analysis on extensive questionnaires, most students responded well to the application of the integration of Alquran to trigonometry. The reason for this is not only the knowledge of spherical trigonometry, Islam through Qur'an verses. This is indicated by the increase in grade performance at each meeting. While the quantitative data analysis of trigonometric learning outcomes data obtained an average pretest value of 45.83 while the posttest average value was 79.42. While for hypothesis testing (one sample t-test) obtained sig. 0,000 which means Ho is rejected. From the results of the analysis, it was concluded that the application of Qur’an integration had a significant effect on trigonometric learning outcomes.